Right to Own Land by the State in the Frame of Constitutional Law - Zainuddin Zainuddin (Randwick International of Social Science Journal, 2021)
The right to control the state over land should be able to achieve the greatest prosperity of the people as mandated by Article 33 paragraph (3) of the 1945 Constitution of the Unitary State of the Republic of Indonesia. It is important to discuss the problem of the meaning of the substance of the right to control land by the State based on the 1945 Constitution. and what is the right to control land by the state based on regulations in the framework of constitutional law so that land for the greatest prosperity of the people can be achieved. The research method used is the normative juridical legal research method. The results show that the right to control land by the state within the framework of constitutional law is still very far from being burned, so that the prosperity of the people, one of which can be achieved through proper management of land controlled by the state, has not been able to achieve people's happiness as adhered to by the theory of utilitarianism law and more. continued as stated in the 1945 Constitution and the Basic Agrarian Law applicable in Indonesia.